Pengaruh faktor risiko pekerja pemanen kelapa sawit terhadap terjadinya keluhan musculoskeletal disorders (MSDS) di PT. Perkebunan Nusantara IV unit Kebun Meranti Paham - -, Hartono; Simatupang, Mega Riama Sawitri Br; Lina, Juliana; Bukit, Rosmeri br; Muharraran, Firdha (Jurnal Kesmas Prima Indonesia, 2023)
Musculoskeletal Disorders (MSDs) are the most common occupational diseases that occur in the working population. The purpose of this study was to determine the effect of risk factors between age, workload, smoking habits and years of service of oil palm harvesters on the occurrence of musculoskeletal disorders. This study used an analytical survey method using a cross sectional design. The research sample is the entire population studied, namely 50 respondents at PT. Perkebunan Nusantara IV Meranti Paham Plantation Unit. The sampling technique used in this study is a total sampling technique where the number of samples is the same as the population. Data was collected using a Nordic Body Map (NBM) questionnaire. The analysis used was univariate, bivariate (Chi-square test) and multivariate analysis. The results of the bivariate analysis showed that there was a strong relationship between age and complaints of musculoskeletal disorders and the results also showed that there was a strong relationship between years of service and complaints of musculoskeletal disorders. The results of the multivariate analysis of the most dominant variable affecting musculoskeletal complaints were years of service after controlling for the age variable. So it was concluded that there was an influence between age and tenure with complaints of musculoskeletal disorders in oil palm harvesters. The most dominant factor for musculoskeletal complaints is years of service.